School Marketing Management based on Customer Preferences in an Educational Setting - Rusdiah, Nadira; Sain, Zohaib Hassan; Mundiri, Akmal (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This study aims to understand school marketing management based on customer preferences. It is grounded in the reality that factors such as declining enrollment rates, academic achievement, school facilities, and teacher quality influence parents' decisions in choosing a school. Therefore, this research focuses on how marketing management strategies are formulated based on the preferences of prospective students and their parents. The study employs a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation techniques. The collected data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and verification. The findings reveal that customer preference-based school marketing strategies are implemented through customer preference research and identification, strengthening school image and branding, and continuous evaluation and improvement. Abstrak: Penelitian ini bertujuan untuk memahami manajemen pemasaran sekolah berbasis preferensi pelanggan. Penelitian ini didasari oleh kenyataan bahwa penurunan jumlah pendaftar, prestasi akademik, fasilitas sekolah, dan kualitas guru memengaruhi keputusan orang tua dalam memilih sekolah. Oleh karena itu, penelitian ini difokuskan pada bagaimana strategi manajemen pemasaran berbasis preferensi calon siswa dan orang tua. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan jenis studi kasus. Data dikumpulkan melalui teknik observasi, wawancara mendalam, dan dokumentasi. Data yang telah dikumpulkan selanjutnya dianalisis dengan mengacu pada model analisis data dari Miles dan Huberman, yang mencakup reduksi data, penyajian data, dan verifikasi. Hasil penelitian menunjukkan bahwa strategi pemasaran sekolah berbasis preferensi dilakukan melalui riset dan identifikasi preferensi pelanggan, penguatan citra dan branding sekolah, serta evaluasi dan perbaikan secara berkelanjutan.